Evaluation of Public Private Partnership Projects in Somalia: Case in Mugadishu Airport and Seaport Managed By Turkish Favori and Albayrak Companies - Dahir, Ahmed Mohamed; Afrah, Nor Abdulle (Advances in Social Sciences Research Journal, 2015)
The main objectives of this study are to examine the role of public private partnership projects on infrastructure development and economic growth and explore the challenges facing public private partnership projects managed Turkish companies in Somalia. A descriptive research design was used; the study population was the employees of airport and seaport and merchants in Mogadishu and a sample size of 87 were drawn. A self administered questionnaire was employed to collect the data from respondents and then analyzed by using descriptive statistics with the aid of SPSS. The findings indicated the role of public private partnership played a significant role on the social and infrastructure developments. Establishment of joint ventures under government and privates boosted economic growth significantly through investment and employment creation in Somalia. Finally, the challenges included not only less knowledge to public private partnership undermined and delayed the implementation of these projects directly and it affected on the infrastructure developments currently and in the long run but also inefficiency from the government intervention and its fragile administration causes delays in the projects’ implementations. Therefore, the study underlined public private partnership could be fruitful if the awareness is promoted as well as government refrains from improper involvements.